Incidence and outcomes of cardiogenic shock among women with spontaneous coronary artery dissection. Issue 4 (8th September 2022) - Osman, Mohammed; Syed, Moinuddin; Simpson, Timothy F.; Bhardwaj, Bhaskar; Kheiri, Babikir; Divanji, Punag; Golwala, Harsh; Zahr, Firas; Cigarroa, Joaquin E.
Abstract: Background: There is a paucity of data on cardiogenic shock (CS) incidence and outcomes among patients with spontaneous coronary artery dissection (SCAD). Methods: Women admitted to the hospital for acute myocardial infarction (AMI) with and without SCAD were identified from the United States National Readmission Database from October 1, 2015 to December 31, 2018. We calculated the incidence of CS among women with AMI with and without SCAD and odds for developing CS after adjusting for baseline characteristics. In addition, we report the utilization of percutaneous coronary intervention, mechanical circulatory support, severe disability surrogates, and 30‐day readmission rates. Results: A total of 664, 292 patients admitted for AMI were eligible for analysis, including 6643 patients with SCAD and 657, 649 without SCAD. Patients with SCAD were younger (57 years [interquartile range, IQR 48–68] vs. 71 years [IQR 60–81], p < 0.01) and had fewer comorbidities yet had a higher incidence of CS as compared to patients without SCAD (9% vs. 5%, p < 0.01) and remained at elevated risk after adjusting for baseline comorbidities (adjusted odds ratio 1.5 [95% confidence interval, CI 1.2–1.7]). Among patients who developed CS, those with SCAD had lower in‐hospital mortality than non‐SCAD (31% vs. 39%, p < 0.01), and were more likely to receive mechanical circulatory support. Conclusions: In a nationally representative sample of women admitted for AMI, we found that patients with SCAD had a higher risk of developing CS and required more frequent use of mechanical circulatory support but were more likely to survive to discharge than women suffering AMI from causes other than SCAD.